Call for Contributions: PLAIO #10 (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2025)
PLA as a Strategic Key to Human Resource and Sustainable Labor Market DevelopmentToday's labor market is characterized by rapid change, technological advances, and a constant demand for agility. Companies face the challenge of keeping their employees sustainably employable, effectively recruiting new talent, promoting internal mobility, and managing staff outflows in a meaningful way. At the same time, employees are looking for opportunities to better utilize their skills and experiences, develop personally, and contribute meaningfully to their organization. Prior Learning Assessment (PLA) offers a unique solution in this complex playing field. PLA enables employees' existing knowledge, skills, and learning through experiences to be systematically identified, valued, and formally recognized. This approach not only enhances employee development and mobility but also helps organizations achieve their strategic goals around human capital investment.In the context of Human Resource Development (HRD), PLA offers concrete tools for optimizing recruitment, advancement, and employee development. By providing insight into what employees can already do, PLA contributes to more efficient training paths, targeted talent development, and a strengthened internal learning culture. Moreover, PLA makes it possible to utilize the potential of employees and better position them in a dynamic labor market.The theme of PLAIO’s tenth issue examines how PLA can be used to promote sustainable employability, strengthen the recruitment process, optimize career opportunities within organizations, and facilitate meaningful work. It also looks at the role of PLA in shaping strategic HR policies aimed at investing in and retaining human capital.We seek submissions that focus on innovative approaches, practical examples/case studies, research, and theoretical reflections to address current issues and challenges in the use of PLA in the workplace. The goal of this issue is to examine how PLA can provide inspiration and solutions for employers, employees, and policymakers to build a future labor market together.Submission Deadline: January 15, 2026